CORRELATION BETWEEN MEDICAL STUDENTS’ PERCEPTION ON LEARNING ENVIRONMENT AND STRESS LEVEL - Resti Rahmadika Akbar; Mardiastuti Wahid; Retno Asti Werdhani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Learning environment in medical education is one of several aspect determine students’ academic success. The medical education itself has been the biggest source of depression or stress for students, beside personal, financial, or family problems. The purpose of this study is to assess the correlation between students’ perception on learning environment and stress levels.Methods: This study was a cross sectional study, conducted from December 2016 to April 2017, involving the 1st, 2nd, 3rd, 4th year students of the Faculty of Medicine, Baiturrahmah University (FK UNBRAH), Padang, with a total of 595 students. Students’ perceptions on learning environment were assessed using the Dundee Ready Educational Environment Measure (DREEM) questionnaire and the student stress level was assessed by the questionnaire of Depression Anxiety Stress Scale 42 (DASS 42). Both questionnaires have been validated and available in Bahasa.Results: Respondents involved in this study were 477 (80.1%).The median of the students’s perceptions on their learning environment was 132 (92-200), which means "more positive than negative". Students’ perceptions on learning environment between 1st year students with other academic years differed significantly. There was no significant difference between female and male students' perceptions on the learning environment. The median value of student stress level of FK UNBRAH was categorized as normal. There was no statistically significant difference in stress level based on academic level and gender. The correlation between students’ perception toward learning environment and academic level was found to be significant with very weak negative correlation (p<0,05)Conclusion: The better students’ perception on the learning environment, the lower the stress level.